An improved LSB-based RDH technique with better reversibility. (2017) - Mondal, Jayanta; Swain, Debabala; Singh, Dushant P.; Mohanty, Sharmila
Lossless image recovery has significant importance in image transmission and security. In this aspect, lots of reversible data hiding (RDH) techniques are available as literature. Still ample measures can be adhered to achieve better reversibility. This paper presents an improved reversible RDH technique to perform a quantitative study to evaluate the recovery of sent image without any distortion. In reversible data hiding, the original image has to go through the encryption and embedding process before transmitting to the receiver. In the proposed RDH technique, a series of computations are done on the three LSB to embed secret bits in the encrypted image. Similarly, the reverse computations are performed on the LSBs to extract the original image content from the decrypted image. Experimental analysis proves the achievement of the proposed technique through different parameters like, PSNR, SSIM, etc.